(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2026)
The rapid development of science and technology has provided both opportunities and challenges for adolescents. Increased access to digital information, including pornographic content, may influence students’ sexual behavior during puberty and potentially lead to risky behaviors that negatively affect reproductive health. This situation reflects a lack of self-regulation among students, which is a key aspect of the independence dimension in the Pancasila Student Profile. This study aimed to develop and evaluate Qur’an-integrated teaching materials on the human reproductive system to strengthen students’ learning autonomy and self-regulation. This research employed a Research and Development (R&D) approach using the ADDIE model. The study involved two groups consisting of an experimental class and a control class selected through purposive sampling. Data were collected using a student questionnaire and analyzed using t-test and N-gain analysis to examine the effectiveness of the developed teaching materials. The results showed that the experimental class achieved an N-gain score of 0.62 (moderate category), while the control class obtained 0.08 (low category). These findings indicate that the Qur’an-integrated teaching materials were more effective in improving students’ independence compared to conventional learning materials. The developed materials integrate scientific concepts of the human reproductive system with Qur’anic values to promote both conceptual understanding and character development. This study contributes to science education by providing an alternative approach to integrating religious values into biology learning to support students’ self-regulation and responsible behavior.